2021
DOI: 10.1093/jb/mvab008
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lncRNA SNHG5 relieves sepsis-induced acute kidney injury by regulating the miR-374a-3p/TLR4/NF-κB pathway

Abstract: Sepsis is an acute systemic infectious disease engendered by infectious factors, which can cause the dysfunction of multiple organs, including acute kidney injury (AKI). Recently, more and more researchers are focusing on long non-coding RNA (lncRNA) that is closely associated with the development and progression of various diseases; however, the role and mechanism of lncRNA in sepsis-induced acute kidney injury is not fully understood. Here, we found a significant increase in the expression of lncRNA small nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Beside miR-320, there are many other miRNAs that were strongly deregulated in the patient populations. Of the most upregulated miRNAs, miR-374a-3p and miR-15a-3p are involved in acute kidney and neuroinflammation, respectively, whereas mir-4721 was proposed as one of the miRNA molecular diagnostic markers for liver fibrosis in patients with chronic hepatitis B [ 36 , 37 , 38 ]. Of the most downregulated miRNAs, miR-4747-3p was found upregulated in Alzheimer’s Disease and hsa-miR-4429 was suggested as a potential diagnostic biomarker for biliary atresia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beside miR-320, there are many other miRNAs that were strongly deregulated in the patient populations. Of the most upregulated miRNAs, miR-374a-3p and miR-15a-3p are involved in acute kidney and neuroinflammation, respectively, whereas mir-4721 was proposed as one of the miRNA molecular diagnostic markers for liver fibrosis in patients with chronic hepatitis B [ 36 , 37 , 38 ]. Of the most downregulated miRNAs, miR-4747-3p was found upregulated in Alzheimer’s Disease and hsa-miR-4429 was suggested as a potential diagnostic biomarker for biliary atresia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the silencing of SNHG5, all these adverse effects caused by high glucose can be improved accordingly. Indeed, downregulation of SNHG5 can inhibit the levels of various inflammatory factors in HK-2 cells, which has been proved by Wang et al [14]. Taken together, downregulation of SNHG5 can alleviate the damage caused by hyperglycemia to HK2 cells to some extent.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, the SNHG5 level of NCM460 cells cultured with high glucose and high lipid in vitro was significantly increased, and the upregulated SNHG5 inhibited cell proliferation and promoted cell apoptosis markedly [13]. Another study revealed that SNHG5 may play a regulatory role in sepsis induced acute kidney injury by regulating the miR-374a-3p/TLR4/NF-κB pathway [14]. To some extent, these studies have shown evidence of SNHG5 and diabetes and kidney damage, but up to now, there are still relatively few studies on the relationship between SNHG5 and DN.…”
Section: Introductionmentioning
confidence: 95%
“…Earlier studies showed that IGFALS might be a useful diagnostic and therapeutic target for HCC [37] and that SORBS2 can accurately predict prognosis of HCC patients [38]. IGFALS has also been identified as a tumor suppressor gene, which is silenced by methylation in HCC [39,40].…”
Section: Discussionmentioning
confidence: 99%